2018
DOI: 10.3390/environments5110121
|View full text |Cite
|
Sign up to set email alerts
|

Community Perceptions of Ecosystem Services and the Management of Mt. Marsabit Forest in Northern Kenya

Abstract: Identifying and characterizing ecosystem services (ES) has been shown to have an important role in sustainable natural resource management. However, understanding communities’ perspectives is critical in determining opportunities and constraints for ES management in multi-use landscapes. To do so, a study was conducted around Mt. Marsabit forest, a multiuse landscape in Kenya. Using stratification, participants from 11 administrative locations adjacent to the forest were selected. A total of 265 households wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 39 publications
2
24
1
4
Order By: Relevance
“…Moreover, plant parts were used in traditional medicine. Therefore, the high level of provisioning service identification was justified by their direct implications on the physical, economic, and social well-being of the community [43]. Moreover, the level of poverty was an important factor in identifying provisioning services, confirming that the poorest people relied more on provisioning services from ecosystems for their daily subsistence.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, plant parts were used in traditional medicine. Therefore, the high level of provisioning service identification was justified by their direct implications on the physical, economic, and social well-being of the community [43]. Moreover, the level of poverty was an important factor in identifying provisioning services, confirming that the poorest people relied more on provisioning services from ecosystems for their daily subsistence.…”
Section: Discussionmentioning
confidence: 99%
“…Factors affecting people’s dependence on forests or their attitudes towards forest management or conservation have been examined extensively using both spatial and social variables. From a socio-economic viewpoint, a number of studies have revealed that educated people, as well as poor people, valued forest ecosystem services more, albeit sometimes in different ways [34, 43]. Demographic characteristics, family size, gender, and age have also been reported to influence the dependence of local communities on the forest and thus their perceptions of ecosystem services [43, 44].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations